Linguo-Stylistic Analysis of Media Texts Concerning the LGBT Community Published in the Online Newspaper “Dnevnik” Between 2008 and 2012 - Georgiev, Alexander (Media and Language, 2019)
The article analyses the various nominations for homosexual men and women, bisexual and transgender people as well as collective nominations for the LGBT community and its subcategories. The frequency with which some nominations occur throughout the 5-year period has been noted.